A conductive paste based on silver-coated hollow COF@PANI

By using silver-coated hollow COF@PANI and other materials in solar cell conductive paste, the problems of poor conductivity and low photoelectric conversion efficiency in existing conductive silver paste are solved, and more efficient photoelectric conversion and more stable structure, while reducing costs.

CN118866427BActive Publication Date: 2025-02-14JIANGSU RIYU PHOTOVOLTAIC NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411347883.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-14
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The contact area of ​​the spherical silver powder and sheet silver powder in the conductive silver paste of existing solar cells decreases during the sintering process, resulting in poor conductivity and insufficient photoelectric conversion efficiency.

Method used

The silver-coated hollow COF@PANI is used as the main material for conductive paste. The specific surface area and conductivity of the material are improved through silver-coated technology, and prepared in combination with glass powder, organic carrier and pure silver powder to form excellent conductivity and photoelectricity. Conversion efficiency.

Benefits of technology

It significantly improves the photoelectric conversion efficiency of solar cells, enhances the conductivity and structural stability, and at the same time reduces the use of silver powder, reduces production costs, and improves the corrosion resistance and oxidation resistance of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of solar cells, and discloses a conductive paste based on silver-coated hollow COF@PANI. The conductive paste of the present invention is prepared based on silver-coated hollow COF@PANI, glass powder, organic carrier, solvent and pure silver powder; the silver-coated hollow COF@PANI has a unique hollow structure, which increases the specific surface area of ​​the silver powder, thereby improving the photoelectric conversion efficiency of the solar cell; wherein, the active groups on the surface of the hollow COF@PANI material can react with silver ions to form a silver ion complex, so that the silver powder has excellent stability and maintains a large specific surface area; and after the aniline layer and the COF layer are made into a conductive paste, they will form a carbon layer and a skeleton structure through high-temperature sintering, and the skeleton structure and the carbon layer can improve the stability of the hollow structure of the silver powder through synergistic action. Therefore, the above-mentioned silver-coated hollow COF@PANI is applied in the conductive paste with excellent conductive properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, and in particular to a conductive paste based on silver-coated hollow COF@PANI. Background Art

[0002] Silver powder is an important material in the electrical and electronic industries and is a basic functional material for electronic pastes such as resistors and ceramics. Silver powder is soft and its ductility is second only to gold. It has excellent electrical and thermal conductivity and is suitable for use in the photovoltaic field.

[0003] Solar cell paste is mainly made by screen printing technology, and grid threads are printed on both sides of the silicon wafer respectively, and then dried and sintered as the electrode of the solar cell. Conductive silver paste is the main material in solar cells, which is mainly composed of conductive silver powder, organic resin and organic solvent, among which the conductive silver powder mainly includes spherical silver powder and flaky silver powder. Although both spherical silver powder and flaky silver powder have a certain conductivity, thus giving the conductive paste a certain photoelectric conversion efficiency, with the increase of actual demand, the photoelectric conversion efficiency brought by spherical silver powder and flaky silver powder no longer meets the actual application needs. For example: the conductive paste prepared by flaky silver powder greatly reduces the contact area of ​​the powder during the sintering process, resulting in a weakened mass transfer effect, so that the film layer has many holes after sintering, the sintering degree is low, and finally the conductive performance is poor. Therefore, it is necessary to provide a silver powder and apply it in the conductive paste, and use the large specific surface area and excellent conductivity of the silver powder to obtain a conductive paste with excellent conductivity, thereby improving the photoelectric conversion efficiency of solar cells. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a conductive paste based on silver-coated hollow COF@PANI.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A conductive paste based on silver-coated hollow COF@PANI, comprising the following raw materials in percentage by mass: 20%-30% silver-coated hollow COF@PANI, 50%-70% pure silver powder, 2%-5% glass powder, 4%-8% acrylic resin, and 3%-7% dodecyl alcohol ester;

[0007] The glass powder is made of Bi-B-Si system glass through melting, heat preservation, sheet pressing and ball milling;

[0008] The conductive paste is prepared by the following steps: weighing raw materials according to mass percentage, mixing the above-mentioned silver-coated hollow COF@PANI (where COF is a covalent organic framework structure), pure silver powder, glass powder, acrylic resin and dodecyl alcohol ester evenly, and then rolling them on a three-roller mill. When the fineness is 10-14μm (the fineness is measured by a scraper fineness meter), the conductive paste is obtained.

[0009] The preparation method of the silver-coated hollow COF@PANI comprises the following steps:

[0010] Step A1: Add ammonium persulfate to deionized water and stir to mix evenly, and adjust the pH to 2.5, which is recorded as solution A; then add nano-silicon dioxide to deionized water and ultrasonically treat for 30 minutes, continue stirring for 1 hour, and then adjust the pH to 2.5, then add aniline and p-phenylenediamine and stir for 30 minutes, and then slowly add solution A in an ice water bath. After the addition is completed, continue stirring to react for 2-4 hours. After the reaction is completed, filter and dry to obtain PANI@SiO2 material;

[0011] Step A2: Add p-phenylenediamine, 2,5-diaminobenzoic acid and triethylamine to N,N-dimethylformamide and disperse them evenly, then add cyanuric chloride and PANI@SiO2 material and ultrasonically disperse for 30 minutes, then transfer to an autoclave for reaction, wash and dry after the reaction is completed, and obtain COF@PANI@SiO2 material;

[0012] Step A3: Add hydrofluoric acid, methanol and deionized water to the reactor containing COF@PANI@SiO2 material in sequence, etch for 4-8 hours to remove SiO2, filter after etching, and wash with methanol and water for multiple times until the solution is neutral, then collect the product and vacuum dry to obtain the hollow COF@PANI material;

[0013] Step A4: Disperse silver nitrate evenly in N, N-dimethylformamide, which is referred to as solution B; then add the hollow COF@PANI material to N, N-dimethylformamide and stir evenly, slowly drop solution B under stirring, continue stirring for 10 minutes after the dropwise addition is completed, adjust the solution pH to 10-11, then add 80wt% hydrazine hydrate, stir and react at 40°C for 20-50 minutes, after the reaction is completed, filter and wash, collect the product, and soak it in ethanol for 2 hours, filter and vacuum dry, and obtain the silver-coated hollow COF@PANI;

[0014] Further, in step A1, the usage ratio of nano-silica, deionized water, aniline, p-phenylenediamine and solution A is 1-3 g: 100 mL: 5-10 mL: 0.5-1.5 g: 10 mL;

[0015] Further, in step A1, the ratio of ammonium persulfate to deionized water in solution A is 5-10 g:10 mL;

[0016] Further, in step A2, the dosage ratio of p-phenylenediamine, 2,5-diaminobenzoic acid, triethylamine, N,N-dimethylformamide, cyanuric chloride and PANI@SiO2 material is 0.1 mol: 0.15-0.25 mol: 15-45 mL: 300 mL: 0.05-0.15 mol: 0.5-2 g;

[0017] Further, in step A2, the reaction temperature in the autoclave is 100-130° C., and the reaction time is 16-20 h;

[0018] Further, in step A3, the ratio of hydrofluoric acid, methanol, deionized water and COF@PANI@SiO2 material in the reactor is 7.5-10mL: 20-30mL: 15mL: 0.5-1g;

[0019] Further, in step A4, the usage ratio of the hollow COF@PANI material, N,N-dimethylformamide, solution B and hydrazine hydrate is 40-100 g: 50 mL: 100 mL: 80-120 mL;

[0020] Furthermore, the usage ratio of silver nitrate and N,N-dimethylformamide in solution B of step A4 is 0.005-0.02 mol:100 mL.

[0021] Beneficial effects of the present invention:

[0022] The conductive paste of the present invention is prepared based on silver-coated hollow COF@PANI, glass powder, organic carrier, solvent and pure silver powder, and has excellent conductive performance and photoelectric conversion efficiency when applied in solar cells.

[0023] The silver-coated hollow COF@PANI is prepared by coating a layer of polyaniline on the surface of silicon dioxide under the action of the initiator ammonium persulfate to synthesize the PANI@SiO2 material; then the amino group on the surface of the PANI@SiO2 material reacts with the -Cl group in COF to form an -NH- chemical bond for connection, so that the two are tightly combined to synthesize the COF@PANI@SiO2 material; then hydrofluoric acid is used for etching to remove SiO2 in the COF@PANI@SiO2 material to synthesize the hollow COF@PANI material; then silver nitrate is used as a silver source to complex silver ions on the surface of the hollow COF@PANI material, and hydrazine hydrate is used as a reducing agent to reduce the silver ions on the surface of the hollow COF@PANI material into silver to synthesize the silver-coated hollow COF@PANI. After the silver-coated hollow COF@PANI is applied to the conductive paste of solar cells, it can effectively improve the photoelectric conversion efficiency of solar cells; the silver-coated hollow COF@PANI has a unique hollow structure, which improves the photoelectric conversion efficiency of solar cells. This is because the hollow structure can provide a larger specific surface area, which is conducive to the absorption and conversion of light energy. At the same time, the structure can also enhance the scattering and reflection of light, so that more light energy is absorbed and utilized by the battery, thereby improving the photoelectric conversion efficiency; the active groups (such as amino, carboxyl, etc.) contained on the surface of the hollow COF@PANI material chelate silver ions to form a stable silver ion complex, thereby Silver ions are stably present on the surface of the hollow COF@PANI material to facilitate the reduction of silver ions and achieve silver powder coating. The silver powder coated in this way has excellent stability and is not easy to collapse during the subsequent sintering process, thereby maintaining a large specific surface area. In addition, after the aniline layer and COF layer in the silver-coated hollow COF@PANI are made into a conductive paste, a carbon layer will be formed after high-temperature sintering. The presence of the carbon layer can not only improve the conductivity of the silver powder, but also stabilize the hollow structure of the silver powder. After sintering, COF forms a stable skeleton structure. The skeleton structure and the carbon layer can synergistically improve the stability of the hollow structure of the silver powder. In addition, this structure can also reduce costs by reducing the amount of silver powder used. This is because the hollow structure can reduce the total volume and weight of the silver powder while maintaining the same conductive properties, thereby reducing the production cost of the conductive silver paste. At the same time, the silver powder with a hollow structure can also enhance the corrosion resistance and oxidation resistance of solar cells, extend their service life, and improve the overall performance and reliability of solar cells. ‌ DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] The preparation method of silver-coated hollow COF@PANI comprises the following steps:

[0027] Step A1: Add 5 g of ammonium persulfate to 10 mL of deionized water and stir to mix evenly, and adjust the pH to 2.5, which is referred to as solution A; then add 1 g of nano-silicon dioxide to 100 mL of deionized water and ultrasonically treat for 30 min, continue stirring for 1 h, then adjust the pH to 2.5, then add 5 mL of aniline and 0.5 g of p-phenylenediamine and stir for 30 min, then slowly add 10 mL of solution A in an ice water bath, continue stirring and react for 2 h after the addition is completed, filter and dry after the reaction is completed, and obtain PANI@SiO2 material;

[0028] Step A2: 0.1 mol p-phenylenediamine, 0.15 mol 2,5-diaminobenzoic acid, and 15 mL triethylamine were added to 300 mL N,N-dimethylformamide and dispersed evenly, and then 0.05 mol cyanuric chloride and 0.5 g PANI@SiO2 material were added and ultrasonically dispersed for 30 min, and then transferred to an autoclave and reacted at 100 ° C for 16 h. After the reaction was completed, the COF@PANI@SiO2 material was washed and dried to obtain the COF@PANI@SiO2 material;

[0029] Step A3: 7.5 mL of hydrofluoric acid, 20 mL of methanol and 15 mL of deionized water were added to a reactor containing 0.5 g of COF@PANI@SiO2 material in sequence, and SiO2 was removed by etching for 4 h. After the etching was completed, the solution was filtered and washed with methanol and water for multiple times until the solution was neutral. The product was then collected and dried in vacuo to obtain a hollow COF@PANI material.

[0030] Step A4: 0.005 mol of silver nitrate was evenly dispersed in 100 mL of N, N-dimethylformamide, which was recorded as solution B; then 40 g of hollow COF@PANI material was added to 50 mL of N, N-dimethylformamide and stirred evenly, and 100 mL of solution B was slowly added dropwise under stirring. After the addition was completed, stirring was continued for 10 min, the pH of the solution was adjusted to 10, and 80 mL of 80 wt% hydrazine hydrate was added. The reaction was stirred at 40 ° C for 20 min. After the reaction was completed, the product was filtered, washed, collected, and soaked in ethanol for 2 h, then filtered and vacuum dried to obtain silver-coated hollow COF@PANI.

[0031] Example 2

[0032] The preparation method of silver-coated hollow COF@PANI comprises the following steps:

[0033] Step A1: Add 7.5g of ammonium persulfate to 10mL of deionized water, stir and mix evenly, and adjust the pH to 2.5, which is recorded as solution A; then add 2g of nano-silicon dioxide to 100mL of deionized water, ultrasonically treat for 30min, continue stirring for 1h, then adjust the pH to 2.5, then add 7.5mL of aniline and 1g of p-phenylenediamine, stir for 30min, and then slowly add 10mL of solution A in an ice water bath. After the addition is completed, continue stirring and react for 3h. After the reaction is completed, filter and dry to obtain PANI@SiO2 material;

[0034] Step A2: 0.1 mol of p-phenylenediamine, 0.2 mol of 2,5-diaminobenzoic acid, and 25 mL of triethylamine were added to 300 mL of N,N-dimethylformamide and dispersed evenly, and then 0.01 mol of cyanuric chloride and 1 g of PANI@SiO2 material were added and ultrasonically dispersed for 30 min, and then transferred to an autoclave and reacted at 110 ° C for 18 h. After the reaction was completed, the COF@PANI@SiO2 material was washed and dried to obtain the COF@PANI@SiO2 material;

[0035] Step A3: 8.5 mL of hydrofluoric acid, 25 mL of methanol and 15 mL of deionized water were added to a reactor containing 0.75 g of COF@PANI@SiO2 material in sequence, and SiO2 was removed by etching for 6 h. After the etching was completed, the solution was filtered and washed with methanol and water for multiple times until the solution was neutral. The product was then collected and dried in vacuo to obtain a hollow COF@PANI material.

[0036] Step A4: 0.01 mol of silver nitrate was evenly dispersed in 100 mL of N, N-dimethylformamide, which was recorded as solution B; then 60 g of hollow COF@PANI material was added to 50 mL of N, N-dimethylformamide and stirred evenly, and 100 mL of solution B was slowly added dropwise under stirring. After the addition was completed, stirring was continued for 10 min, the pH of the solution was adjusted to 10.5, and 100 mL of 80 wt% hydrazine hydrate was added. The reaction was stirred at 40 ° C for 30 min. After the reaction was completed, the product was filtered, washed, collected, and soaked in ethanol for 2 h, then filtered and vacuum dried to obtain silver-coated hollow COF@PANI.

[0037] Example 3

[0038] The preparation method of silver-coated hollow COF@PANI comprises the following steps:

[0039] Step A1: Add 9g of ammonium persulfate to 10mL of deionized water and stir to mix evenly, and adjust the pH to 2.5, which is recorded as solution A; then add 2.5g of nano-silicon dioxide to 100mL of deionized water and ultrasonically treat for 30min, continue stirring for 1h, then adjust the pH to 2.5, then add 9mL of aniline and 1.5g of p-phenylenediamine and stir for 30min, then slowly add 10mL of solution A in an ice water bath, continue stirring and react for 4h after the addition is completed, filter and dry after the reaction is completed to obtain PANI@SiO2 material;

[0040] Step A2: 0.1 mol p-phenylenediamine, 0.25 mol 2,5-diaminobenzoic acid, and 35 mL triethylamine were added to 300 mL N,N-dimethylformamide and dispersed evenly, and then 0.15 mol cyanuric chloride and 1.5 g PANI@SiO2 material were added and ultrasonically dispersed for 30 min, and then transferred to an autoclave and reacted at 120 ° C for 18 h. After the reaction was completed, the COF@PANI@SiO2 material was washed and dried to obtain the COF@PANI@SiO2 material;

[0041] Step A3: 9 mL of hydrofluoric acid, 30 mL of methanol and 15 mL of deionized water were added to a reactor containing 0.9 g of COF@PANI@SiO2 material in sequence, and SiO2 was removed by etching for 8 h. After the etching was completed, the solution was filtered and washed with methanol and water for multiple times until the solution was neutral. The product was then collected and dried in vacuo to obtain a hollow COF@PANI material.

[0042] Step A4: 0.015 mol of silver nitrate was evenly dispersed in 100 mL of N, N-dimethylformamide, which was recorded as solution B; then 80 g of hollow COF@PANI material was added to 50 mL of N, N-dimethylformamide and stirred evenly, and 100 mL of solution B was slowly added dropwise under stirring. After the addition was completed, stirring was continued for 10 min, the pH of the solution was adjusted to 10.5, and 120 mL of 80 wt% hydrazine hydrate was added. The reaction was stirred at 40 ° C for 40 min. After the reaction was completed, the product was filtered, washed, collected, and soaked in ethanol for 2 h, then filtered and vacuum dried to obtain silver-coated hollow COF@PANI.

[0043] Example 4

[0044] The preparation method of silver-coated hollow COF@PANI comprises the following steps:

[0045] Step A1: Add 10g of ammonium persulfate to 10mL of deionized water and stir to mix evenly, and adjust the pH to 2.5, which is recorded as solution A; then add 3g of nano-silicon dioxide to 100mL of deionized water and ultrasonically treat for 30min, continue stirring for 1h, then adjust the pH to 2.5, then add 10mL of aniline and 1.5g of p-phenylenediamine and stir for 30min, then slowly add 10mL of solution A in an ice water bath, continue stirring and react for 4h after the addition is completed, filter and dry after the reaction is completed to obtain PANI@SiO2 material;

[0046] Step A2: 0.1 mol p-phenylenediamine, 0.25 mol 2,5-diaminobenzoic acid, and 45 mL triethylamine were added to 300 mL N,N-dimethylformamide and dispersed evenly, and then 0.15 mol cyanuric chloride and 2 g PANI@SiO2 material were added and ultrasonically dispersed for 30 min, and then transferred to an autoclave and reacted at 130 ° C for 20 h. After the reaction was completed, the COF@PANI@SiO2 material was washed and dried to obtain the COF@PANI@SiO2 material;

[0047] Step A3: 10 mL of hydrofluoric acid, 30 mL of methanol and 15 mL of deionized water were added to a reactor containing 1 g of COF@PANI@SiO2 material in sequence, and SiO2 was removed by etching for 8 h. After the etching was completed, the solution was filtered and washed with methanol and water for multiple times until the solution was neutral. The product was then collected and dried in vacuo to obtain a hollow COF@PANI material.

[0048] Step A4: 0.02 mol of silver nitrate was evenly dispersed in 100 mL of N, N-dimethylformamide, which was recorded as solution B; then 100 g of hollow COF@PANI material was added to 50 mL of N, N-dimethylformamide and stirred evenly, and 100 mL of solution B was slowly added dropwise under stirring. After the addition was completed, stirring was continued for 10 min, the pH of the solution was adjusted to 11, and 120 mL of 80 wt% hydrazine hydrate was added. The reaction was stirred at 40 ° C for 50 min. After the reaction was completed, the product was filtered, washed, collected, and soaked in ethanol for 2 h, then filtered and vacuum dried to obtain silver-coated hollow COF@PANI.

[0049] Example 5

[0050] A conductive paste based on silver-coated hollow COF@PANI is prepared by the following steps:

[0051] 20% silver-coated hollow COF@PANI prepared in Example 1, 70% pure silver powder, 2% glass powder, 4% acrylic resin, 4% dodecyl alcohol ester;

[0052] The raw materials were weighed according to the mass percentage, and the silver-coated hollow COF@PANI, pure silver powder, glass powder, acrylic resin and dodecyl alcohol prepared in Example 1 were mixed evenly and then placed on a three-roll mill for rolling. When the fineness thereof was 10 μm as measured by a scraper fineness meter, a conductive slurry was obtained. The glass powder was a Bi-B-Si system glass obtained by melting, heat preservation, tableting and ball milling.

[0053] Example 6

[0054] A conductive paste based on silver-coated hollow COF@PANI is prepared by the following steps:

[0055] 24% silver-coated hollow COF@PANI prepared in Example 2, 66% pure silver powder, 3% glass powder, 4% acrylic resin, and 3% dodecanol ester;

[0056] The raw materials were weighed according to the mass percentage, and the silver-coated hollow COF@PANI, pure silver powder, glass powder, acrylic resin and dodecyl alcohol prepared in Example 2 were mixed evenly and then placed on a three-roll mill for rolling. When the fineness thereof was 12 μm as measured by a scraper fineness meter, a conductive slurry was obtained. The glass powder was a Bi-B-Si system glass obtained by melting, heat preservation, tableting and ball milling.

[0057] Example 7

[0058] A conductive paste based on silver-coated hollow COF@PANI is prepared by the following steps:

[0059] 27% silver-coated hollow COF@PANI prepared in Example 3, 60% pure silver powder, 4% glass powder, 6% acrylic resin, and 3% dodecyl alcohol ester;

[0060] The raw materials were weighed according to the mass percentage, and the silver-coated hollow COF@PANI, pure silver powder, glass powder, acrylic resin and dodecyl alcohol prepared in Example 3 were mixed evenly and then placed on a three-roll mill for rolling. When the fineness thereof was 13 μm as measured by a scraper fineness meter, a conductive slurry was obtained. The glass powder was Bi-B-Si system glass obtained by melting, heat preservation, tableting and ball milling.

[0061] Example 8

[0062] A conductive paste based on silver-coated hollow COF@PANI is prepared by the following steps:

[0063] 30% silver-coated hollow COF@PANI prepared in Example 4, 50% pure silver powder, 5% glass powder, 8% acrylic resin, and 7% dodecanol ester;

[0064] The raw materials were weighed according to the mass percentage, and the silver-coated hollow COF@PANI, pure silver powder, glass powder, acrylic resin and dodecyl alcohol prepared in Example 4 were mixed evenly and then placed on a three-roll mill for rolling. When the fineness thereof was 14 μm as measured by a scraper fineness meter, a conductive slurry was obtained. The glass powder was a Bi-B-Si system glass obtained by melting, heat preservation, tableting and ball milling.

[0065] Comparative Example 1

[0066] This comparative example is a conductive paste, which is different from Example 8 in that the hollow silver powder is used to replace the silver-coated hollow COF@PANI prepared in Example 4, and the rest are the same;

[0067] The modified silver powder is prepared by the following steps:

[0068] Step S1: 0.015 mol of silver nitrate is dispersed evenly in 100 mL of N, N-dimethylformamide, which is recorded as solution B; then 80 g of nano-silicon dioxide is added to 50 mL of N, N-dimethylformamide and stirred evenly, 100 mL of solution B is slowly added dropwise under stirring, and after the addition is completed, stirring is continued for 10 min, the pH of the solution is adjusted to 10.5, and then 120 mL of 80 wt% hydrazine hydrate is added, and the reaction is stirred at 40 ° C for 40 min. After the reaction is completed, the product is filtered, washed, collected, and soaked in ethanol for 2 h, and then filtered and vacuum dried to obtain Ag@SiO2 material;

[0069] Step S2: 8.5 mL of hydrofluoric acid, 25 mL of methanol and 15 mL of deionized water are added sequentially into a reactor containing 0.75 g of Ag@SiO2 material, and SiO2 is removed by etching for 6 h. After the etching is completed, the solution is filtered and washed with methanol and water for multiple times until the solution is neutral. The product is then collected and dried in vacuo to obtain hollow silver powder.

[0070] Comparative Example 2

[0071] This comparative example is a conductive paste, which is different from Example 8 in that the silver-coated hollow carbon material is used instead of the silver-coated hollow COF@PANI prepared in Example 4, and the rest are the same;

[0072] The silver-coated hollow carbon material is prepared by the following steps:

[0073] Step S1: Add 7.5g of ammonium persulfate to 10mL of deionized water, stir and mix evenly, and adjust the pH to 2.5, which is recorded as solution A; then add 2g of nano-silicon dioxide to 100mL of deionized water, ultrasonically treat for 30min, continue stirring for 1h, then adjust the pH to 2.5, then add 7.5mL of aniline and 1g of p-phenylenediamine, stir for 30min, and then slowly add 10mL of solution A in an ice water bath. After the addition is completed, continue stirring and react for 3h. After the reaction is completed, filter and dry to obtain PANI@SiO2 material;

[0074] Step S2: 8.5 mL of hydrofluoric acid, 25 mL of methanol and 15 mL of deionized water were added to a reactor containing 0.75 g of PANI@SiO2 material in sequence, and SiO2 was removed by etching for 6 h. After the etching was completed, the solution was filtered and washed with methanol and water for multiple times until the solution was neutral. The product was then collected and dried in vacuo to obtain a hollow PANI material.

[0075] Step S3: 0.01 mol of silver nitrate was evenly dispersed in 100 mL of N, N-dimethylformamide, which was recorded as solution B; then 60 g of the hollow PANI material was added to 50 mL of N, N-dimethylformamide and stirred evenly, and 100 mL of solution B was slowly added dropwise under stirring. After the addition was completed, stirring was continued for 10 min, the pH of the solution was adjusted to 10.5, and 100 mL of 80 wt% hydrazine hydrate was added. The reaction was stirred at 40 ° C for 30 min. After the reaction was completed, the product was filtered, washed, collected, and soaked in ethanol for 2 h, then filtered and vacuum dried to obtain the hollow Ag@PANI material;

[0076] Step S4: placing the hollow Ag@PANI material into a tubular furnace, heating it to 900°C at a heating rate of 2°C / min under nitrogen conditions, and sintering it for 2.5h to obtain a silver-coated hollow carbon material.

[0077] After printing the conductive pastes prepared in Examples 5-8 and Comparative Examples 1-2, solar cells were prepared. The photoelectric conversion efficiency of the solar cells was tested, and the conversion efficiency was tested using a German Berger tester PSS10-HE.

[0078] The test results are shown in the following table:

[0079]

[0080] As can be seen from the above table, the silver powder prepared by the present invention is applied to conductive silver paste, and then the conversion efficiency of the solar cell prepared by the conductive silver paste is tested. It is found that the conversion efficiency ranges from 25.42% to 25.66%, indicating that the silver powder has excellent conversion efficiency after being applied to solar cells.

[0081] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A conductive paste based on silver-coated hollow COF@PANI, characterized in that: The raw materials include the following mass percentages: 20%-30% silver-coated hollow COF@PANI, 50%-70% pure silver powder, 2%-5% glass powder, 4%-8% acrylic resin, and 3%-7% dodecanol ester; The conductive paste is prepared by the following steps: weighing raw materials according to mass percentage, mixing the above-mentioned silver-coated hollow COF@PANI, pure silver powder, glass powder, acrylic resin and dodecyl alcohol ester evenly, and rolling them on a three-roller mill, and when the fineness is 10-14 μm, the conductive paste is obtained; The silver-coated hollow COF@PANI comprises the following steps: Step A1: Add ammonium persulfate to deionized water and stir to mix evenly, and adjust the pH to 2.5, which is recorded as solution A; then add nano-silicon dioxide to deionized water and ultrasonically treat for 30 minutes, continue stirring for 1 hour, then adjust the pH to 2.5, then add aniline and p-phenylenediamine and stir for 30 minutes, and then slowly add solution A under ice water bath conditions, continue stirring to react for 2-4 hours after the addition is completed, filter and dry after the reaction is completed, and obtain PANI@SiO2 material, the amount ratio of nano-silicon dioxide, deionized water, aniline, p-phenylenediamine and solution A is 1-3g:100mL:5-10mL:0.5-1.5g:10mL, and the amount ratio of ammonium persulfate to deionized water in solution A is 5-10g:10mL; Step A2: add p-phenylenediamine, 2,5-diaminobenzoic acid and triethylamine to N,N-dimethylformamide and disperse them evenly, then add cyanuric chloride and PANI@SiO2 material and ultrasonically disperse them for 30 minutes, then transfer to an autoclave for reaction, after the reaction is completed, wash and dry to obtain COF@PANI@SiO2 material, the amount ratio of p-phenylenediamine, 2,5-diaminobenzoic acid, triethylamine, N,N-dimethylformamide, cyanuric chloride and PANI@SiO2 material is 0.1 mol: 0.15-0.25 mol: 15-45 mL: 300 mL: 0.05-0.15 mol: 0.5-2 g, the reaction temperature in the autoclave is 100-130°C, and the reaction time is 16-20 h; Step A3: Add hydrofluoric acid, methanol and deionized water to the reactor containing COF@PANI@SiO2 material in sequence, etch for 4-8 hours to remove SiO2, filter after etching, and wash with methanol and water for multiple times until the solution is neutral, then collect the product and vacuum dry to obtain the hollow COF@PANI material; Step A4: Disperse silver nitrate evenly in N, N-dimethylformamide, recorded as solution B; then add the hollow COF@PANI material to N, N-dimethylformamide and stir evenly, slowly drop solution B under stirring, continue stirring for 10 minutes after the addition is completed, adjust the pH of the solution to 10-11, add 80wt% hydrazine hydrate, and stir at 40°C for 20-50 minutes. After the reaction is completed, filter and wash, collect the product, and soak it in ethanol for 2 hours, then filter and vacuum dry to obtain silver-coated hollow COF@PANI, the amount ratio of hollow COF@PANI material, N, N-dimethylformamide, solution B and hydrazine hydrate is 40-100g:50mL:100mL:80-120mL, and the amount ratio of silver nitrate and N, N-dimethylformamide in solution B is 0.005-0.02mol:100mL.

2. The conductive paste based on silver-coated hollow COF@PANI according to claim 1, characterized in that: The dosage ratio of hydrofluoric acid, methanol, deionized water and COF@PANI@SiO2 material in the reactor in step A3 is 7.5-10mL:20-30mL:15mL:0.5-1g.

3. The conductive paste based on silver-coated hollow COF@PANI according to claim 1, characterized in that: The glass powder is made of Bi-B-Si system glass through melting, heat preservation, sheet pressing and ball milling.

Citation Information

Patent Citations

  • Core-shell structure polyaniline / silver conductive nano composite material and preparation method thereof

    CN101838460A

  • Preparation method and application of conductive imprinting Ag@PANI / CoFe2O4 / C

    CN108745308A